Psychological Characteristics of PSIM Yogyakarta Players in Wading the League 2 Soccer Competition in 2019/2020 - Antonius Tri Wibowo; Asna Syafitri; Dody Tri Iwandana (Journal of Education, Health and Sport, 2019)
This study aims to determine the psychological characteristics of PSIM Yogyakarta players in wading the League 2 competition. Data collected from 27 players who are members of the PSIM Team in 2019 can be concluded that PSIM players totaling 27 people have characteristics for the aspect of motivation with a mean (38.6 ) with a percentage (97%), included in the category (very high). As for the aspect of confidence, PSIM players have an average (30) with a percentage (83%) in the (very high) category. For anxiety control aspect, it has average (27.6) with percentage (79%) and categorized (High), mental preparation aspect has average (18) with percentage (60%) and categorized (Medium), aspect of team attention has average (14) with a percentage (71%) and included in the category (High), and the Concentration aspect had an average (23.8) with a percentage (76%) and included in the category (very High).